ANALISIS PENERAPAN RANCANGAN TESLA COIL PADA LAMPU DI KAPAL - Putri Isrok Wanda Oktavia; Agus Dwi Santoso; Henna Nurdiansari; Akhmad Kasan Gupron (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Electrical energy is distributed using copper cables as an intermediary, from high to low voltage systems, until it is ready for use. Copper cables were chosen to transfer electrical energy because the material is able to conduct electrons that can move freely. In this research the author used a research methodology type of method. This research used the ADDIE type Research and Development (R&D) method. Addie consists of Analysis, Design, Development, Implementation and Evaluation. Several test subjects were carried out on light bulbs, 18 W and 36 W AC TL lamps, 60 W AC incandescent lamps, and 8 W AC LED lamps. It was obtained that lamps that could emit light efficiently were TL lamps because TL lamps can operate at high frequencies. Generated by Tesla Coil. From the calculation of the ship's generator fuel, if all the lights use Tesla coils in MT. Long ship, fuel cost savings to Rp. 3,528,263 which should be Rp. 16,691,589 to Rp. 13,163,325. The research results stated that it had not reached the expected value because the ones that could work efficiently were TL lamps because the Tesla coil was only able to work on lamps that had winding components.